Contribution of carbon and nitrogen to the soil by residues of alternative forage crops - González-Cifuentes, Ana Isabel; Reta-Sanchez, David Guadalupe; Cueto Wong, José Antonio; Sánchez Duarte, Juan Isidro; Ochoa Martínez, Esmeralda; Reyes González, Arturo (Revista Mexicana de Ciencias Agrícolas, 2022)
A greater diversity of forages in autumn-winter increases the input of carbon (C) and nitrogen (N) into the soil in the harvest residues. The objective of the study was to evaluate the potential contribution of C and N to the soil in alternative and traditional forage residues during the autumn-winter cycle. The experiment evaluated the dry matter (DM) yield, quantity of residues and C/N ratio in 11 forage species. The traditional crops oats, barley, triticale, wheat, berseem clover and annual ryegrass contributed less harvest residues (365 to 612 kg ha-1) and of lower quality, with values of the C/N ratio of 23.5 to 42.8. Alternative crops canola, beet, brassicas, radish and chickpea contributed more residues (432 to 2 958 kg ha-1), with higher N contents (18.5 to 32.6 g kg-1) and lower values of the C/N ratio (11.4 to 20). Alternative crops with thickened roots such as beet, brassica and radish improved the quantity and quality of harvest residue contribution, with a potential C capture capacity similar to traditional crops. However, only Winfred brassica and Graza radish obtained DM yields (10 094 to 11 636 kg ha-1) similar to or greater than those observed in the control cereals Cuauhtémoc oats (11 161 kg ha-1) and AN105 triticale (9 644 kg ha-1). A greater diversity of forages can improve in quantity and quality the contribution of harvest residues to the soil.